2008
DOI: 10.1103/physrevc.77.064314
|View full text |Cite
|
Sign up to set email alerts
|

First observation ofα-cluster states in the14O+4et al.

Abstract: We measured 14 O + 4 He excitation functions for elastic scattering which demonstrate, for the first time, a well developed α-cluster structure in the proton rich nucleus, 18 Ne. We present the excitation energies and estimates of the spins for the dominant resonances using an R-matrix approach. A resonance at 9.2 MeV excitation energy in 18 Ne is particularly interesting. The spin-parity of the state is found to be 3 − and the α particle reduced width for the state appears to be comparable to the single parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…A rather narrow level (Γ < 60 keV) is observed at 9.111(25) MeV and a higher-energy peak is also present at 11.58(64) MeV. The lower-energy peak was not observed in an α+ 14 O elastic scattering experiment, where an E * =9.2-MeV level was found, but its width is much larger (Γ=300 keV) [45]. The presence of the wider peak at almost the same energy may have reduced their sensitivity to the level we observed, but on the other hand with its small decay width, it may not have a strong α-cluster structure and thus was not strongly excited in the α-scattering experiment.…”
Section: G Other Exit Channelsmentioning
confidence: 87%
“…A rather narrow level (Γ < 60 keV) is observed at 9.111(25) MeV and a higher-energy peak is also present at 11.58(64) MeV. The lower-energy peak was not observed in an α+ 14 O elastic scattering experiment, where an E * =9.2-MeV level was found, but its width is much larger (Γ=300 keV) [45]. The presence of the wider peak at almost the same energy may have reduced their sensitivity to the level we observed, but on the other hand with its small decay width, it may not have a strong α-cluster structure and thus was not strongly excited in the α-scattering experiment.…”
Section: G Other Exit Channelsmentioning
confidence: 87%
“…For cluster states having an α cluster around a core nucleus, well-known examples are 16 O+α states in 20 Ne and 12 C+α states in 16 O [6]. Recent experimental and theoretical studies have revealed many cluster resonances in highly excited states near the α-decay threshold also in unstable nuclei, for instance, A−4 He+α states in Be isotopes [1,4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], 10 Be+α states in 14 C [27][28][29][30]54], 14 C+α states in 18 O and their mirror states [31][32][33][34][35][36][37][38][39][40], 18 O+α states in 22 Ne [38]…”
Section: Introductionmentioning
confidence: 99%
“…A rather narrow level (Γ < 60 keV) is observed at 9.111 (25) MeV and a higherenergy peak is also present at 11.58(64) MeV. The lowerenergy peak was not observed in an α+ 14 O elastic scattering experiment, where a E * =9.2 MeV level was found, but its width is much larger (Γ=300 keV) [42]. The presence of the wider peak at almost the same energy may have reduced their sensitivity to the level we observed, but on the other hand with its small decay width, it may not have a strong α-cluster structure and thus was not strongly excited in the α-scattering experiment.…”
Section: H Other Exit Channelsmentioning
confidence: 83%